The importance of social cost benefit analysis as a tool to help green economics to allocate resources more efficiently - Yee, Chow Fah; Tan, Eu Chye (Inderscience, 2010)
The authors have used social cost benefit analysis (SCBA) to evaluate a sample of firms in Malaysia to investigate the claims made in support of financial liberalisation. Social prices rather than market prices are used as social prices incorporate both the growth and distributional objectives of the country. Contrary to theory, results showed that the pre liberalization cases are more efficient in terms of achieving the country's objectives. It revealed that banks which employed market orientated mechanisms to allocate resources, did not result in the resources being put to their best possible uses for the period studied. It is time every nation makes a conscientious effort at allocating its resources in a more efficient and equitable manner, in order to live within the boundaries of nature and the planet, putting limited resources to their best possible uses to help achieve a green economy. Copyright © 2010 Inderscience Enterprises Ltd.